2019
DOI: 10.1590/2236-8906-69/2018
|View full text |Cite
|
Sign up to set email alerts
|

Wood-decay fungi (Agaricomycetes, Basidiomycota) in three physiognomies in the Savannah region in Brazil

Abstract: This study was carried out aiming at determining whether the following factors are related to the diversity of wood-decay fungi: cerrado physiognomies, vegetation diversity (availability of substrates), preservation status of the area and its management backgrounds, and the existence of rivers nearby (humidity). 796 specimens were collected in four areas: one in the cerrado sensu stricto, one in the semi-deciduous forest and two in the riparian forest (one more preserved and the other less preserved). A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…As espécies foram encontradas e separadas a partir da formação vegetativa (gráfico 1) em que foram encontradas (tabela 2), sendo a maior parte delas na Mata ripária, localizadas próximas a corpos d'água, assim como no estudo Abrahão et al (2019), onde foi encontrada uma maior riqueza e abundância de Agaricomycetes em floresta ripária preservada. Também houve diferenciação nos substratos das amostras (tabela 3), onde a maioria das espécies não identificadas estavam principalmente presente nas matas de galerias, em regiões onde se encontravam uma grande concentração de serrapilheira, sendo o substrato de 3 das espécies folhas de dicotiledôneas.…”
Section: Resultsunclassified
“…As espécies foram encontradas e separadas a partir da formação vegetativa (gráfico 1) em que foram encontradas (tabela 2), sendo a maior parte delas na Mata ripária, localizadas próximas a corpos d'água, assim como no estudo Abrahão et al (2019), onde foi encontrada uma maior riqueza e abundância de Agaricomycetes em floresta ripária preservada. Também houve diferenciação nos substratos das amostras (tabela 3), onde a maioria das espécies não identificadas estavam principalmente presente nas matas de galerias, em regiões onde se encontravam uma grande concentração de serrapilheira, sendo o substrato de 3 das espécies folhas de dicotiledôneas.…”
Section: Resultsunclassified
“…Our fungi inventory was collected from two forest fragments in the municipality of Poços de Caldas. Ten transects of 200 m² each were demarcated in these fragments, according to the measurements recommended by Zak & Willig (2004) and in a recent study developed in Brazil by Abrahão et al (2019). Sample collection was performed monthly from June/2018 to May/2019, and the first author collected all materials.…”
Section: Sample Collection and Preservationmentioning
confidence: 99%
“…On the other hand, Brazil is home to the world's richest flora (Forzza et al 2012) and includes two biodiversity hotspots: Atlantic Forest and Cerrado (Mittermeier et al 2004;Myers et al 2000). Recent taxonomic studies for the Cerrado biome Abrahão et al 2019;Alvarenga et al 2015;Costa-Rezende et al 2015;Bononi et al 2017;Gibertoni & Drechsler-Santos 2010) listed only 134 Agaricomycetes species from a total of 753 fungi on the site-checklist of the Brazilian Flora 2020 (http://floradobrasil.jbrj.gov.br) for the region.…”
Section: Introductionmentioning
confidence: 99%
“…Tocantins, one of the states partially covered by the Cerrado biome, is the least known state of Brazil, with only 25 species of fungi described for its territory, especially due to a lack of sampling and active groups of mycologists in the area (Maia et al 2015). In addition, the overgrowing deforestation in the biome increases the threat on fungal knowledge, as recent studies have shown that Agaricomycetes diversity within the Cerrado can be influenced by factors such as vegetation, physiognomies and preservation levels in each area (Abrahão et al 2019). Thus, this study aimed to increase the list of lignocellulolytic Agaricomycetes recorded for the Cerrado biome by exploring preserved areas and shedding light on fungal diversity and distribution in them.…”
Section: Introductionmentioning
confidence: 99%